PELATIHAN UNTUK SISWA DALAM PENERAPAN TEKNLOGI BERBASIS AI APLIKASI LUMEN UNTUK PEMBELAJARAN DI SMAN 5 KARAWANG - Septi Fitri Meilana,; Zulfadewina,; Khavisa Pranata, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service Activity (PkM) aims to enhance students' skills in utilizing artificial intelligence (AI)-based technology through the Lumen5 application for interactive learning. The training was conducted at SMAN 5 Karawang on January 21, 2025, involving 40 students as participants. The program included material on the fundamentals of AI, an introduction to the Lumen5 application for creating interactive learning videos, and intensive practice sessions with mentoring to produce engaging and effective learning media. The method employed a combination of synchronous and asynchronous approaches, including interactive lectures, discussions, and hands-on practice. The results of the activity indicated a significant improvement in students' skills in designing and utilizing interactive learning videos based on technology. This training had a positive impact on enhancing students' technological literacy, particularly in integrating AI technology into educational settings